Wegener's granulomatosis: isolated involvement of the trachea and larynx. Issue 8 (August 1987) - Hellmann, D; Laing, T; Petri, M; Jacobs, D; Crumley, R; Stulbarg, M
Abstract : A 26 year old man with subacute hoarseness and stridor was shown to have Wegener's granulomatosis isolated to the trachea and larynx. Although isolated laryngeal Wegener's is unusual, a review of the literature suggests that early treatment with cyclophosphamide is warranted.